Biometria testicular e suas correlações com a avaliação de parâmetros seminais de catetos (Tayassa tajacu Linnaeus, 1758) - Peixoto, Gislayne Christianne Xavier (Universidade Federal Rural do Semi-Árido, 2011)
The wanton destruction of natural forests coupled with poaching in small remaining reserves, have caused enormous damage towildlife populations.These factors have become genuine threats to the species Tayassu tajacu, known as collared peccary. Thus, the application of biotechnologies become basic requirements in the conservation of this species. However, for better application, better understanding is needed of the species' morphophysiology. This study investigated the testicular biometry using different measurement methods and applying different formulas to determine the testicular volume. Still, there was a study of its correlation with semen characteristics, as well as morphometric and proportion of seminiferous tubules. For this purpose we used 10 adult male collared peccary, contained with use of propofol (5mg/kg). Testicular measurements (height, width and length) were initially measured by caliper and then by ultrasound (8 MHz). The results were applied in the formula of Lambert (width x height x length x 0.71), ellipsoid formula (width x height x length x 0.52) and Hansen formula (width x height2 x 0.52), and then compared with the real volume obtained by water displacement, after removal of the testicles. The semen used to assess correlation with biometric data was collected by electroejaculation. To determine the area occupied by seminiferous tubules, testicular fragments were analyzed by classical histology. As main results, observed the average real testicular volume was 22.65 ± 1.52 mL. The formula of Lambert estimated testicular volume more accurately when measurements were obtained by testicular ultrasonography. However, when the caliper was the methodology used, the volumes were closest to the real volume, especially when the ellipsoid formula and formula of Hansen were applied, underestimating the real volume only 1.53 ± 1.75 mL and 1.53 ± 1.65 mL, respectively. The animals showed a large individual variation in relation to testicular morphometry and semen characteristics. In addition, no significant correlation was obtained between testicular measurements and semen characteristics. The histometric analysis revealed that 67.8% of the testis are occupied by seminiferous tubules, with tubular average diameter of 222 ± 27 μm and epithelial height, 70 ± 9.7 μm
Keywords: Tayassu tajacu; Orquidometria; Volume testicular; Ultrassonografia; Paquímetro; Tayassu tajacu; Orchidometer; Tetis volume; Ultrasound; Caliper; CIENCIAS AGRARIAS::MEDICINA VETERINARIA